Effects of the geometry and material properties on the mechanical strength and failure modes of water hydraulic artificial muscles. (22nd June 2021) - Zhang, Zengmeng; Che, Jinkai; Ning, Dayong; Liu, Peipei; Gong, Yongjun
Abstract: To develop high-strength water hydraulic artificial muscle (WHAM) and ensure its reliability, the failure mechanism and the main effect factors of WHAM's strength were studied. WHAM's failure modes consist of end fitting slipping out, fibre sleeve loosening, the end of rubber tube breaking, rubber tube coming out from fibre sleeve and fibre fracture. It can be preliminarily confirmed that the strength of WHAM is mainly related to fibre sleeve, rubber tube and end fitting structure. Therefore, effects of structure and material properties on WHAM's strength and failure modes were analysed. The structure parameters contain the initial braid angle, the number of fibre bundles, the rubber tube wall thickness, the diameter of crimping rings, and the number of crimping rings. The fibre spacing was optimized according to the analysis of the ratio of fibre sleeve coverage area to rubber tube outer wall area. The number of end fitting's barbs and the crimping rings were improved by strength test. Moreover, it can be confirmed that the initial braid angle, fibre sleeve material, rubber tube wall thickness and deformation of rubber tube have strong effects on WHAM's strength. Aiming to obtain the level of significance for effect factors and an appropriate set of structure parameters, the orthogonal experiment with four factors and two levels was designed. The structure parameters of high-strength WHAM were obtained according to the orthogonal analysis, which can provide theoretical guidance for high-strength WHAM design. The tests results show that the improved structure can effectively avoid the failure modes of end fitting slipping out, fibre sleeve loosening, and rubber tube coming out from fibre sleeve. Finally, only two kinds of failure modes, the end of rubber tube breaking and fibre fracture, occurred. The reliability of WHAM can be improved by studying the WHAM's strength and failure modes.